Impact of ESG Disclosure on Stock Volatility and Investor Confidence during covid-19 and Russia-Ukraine conflict. - Chaudhary, Diwakar (My University, 2026)
Description: This thesis examines the ESG (environmental, social and governance) disclosures and how such disclosure affect the stock price fluctuation and investor confidence during COVID-19 pandemic and Russia Ukraine conflict. This thesis uses panel regression, correlation analysis and event study to test its hypotheses. Data from thirty major corporations are collected to conduct the research. This thesis finds that higher ESG disclosure are linked with lower stock price volatility during both COVID-19 and Russia Ukraine war. Specially during pandemic this result was more stronger. Strong ESG reporting also increased investor confidence, as evidenced by increased trading activity, improved analyst ratings, and smaller price gaps between the highest and lowest prices consumers were willing to pay. This is due to the fact that these sectors are more impacted by erratic fluctuations in commodity prices and worldwide political concerns. Investors could benefit from these findings. The result of this thesis show how ESG consideration can help investors during violent market swings. In order to mitigate the risk of price swing study show how corporate executives should report their ESG information thoroughly. The findings encourage policymakers to adopt uniform ESG reporting guidelines in order to improve market stability and transparency. Overall, this study shows that effective ESG reporting is a vital strategy for lowering risks and demonstrating a company's capacity to manage significant global challenges.
Keywords: fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; Master's Degree Programme in Finance